(1334) نموذج مقترح لاستجابة الخصوبة لوفيات الأطفال A proposed model for fertility response to child mortality - مصطفى جلال مصطفى (معهد التخطيط القومى, 2026)
يقدم البحث دراسة تحليلية لظاهرة "الرغبة التعويضية"، وهي ميل الأسر لزيادة الإنجاب لتعويض ما فقدته من أطفال في سن مبكرة، مما يؤدي لارتفاع معدلات الخصوبة التي تعيق خطط التنمية في مصر، يوضح البحث أن هذه الاستجابة تختلف من أسرة لأخرى بناءً على عوامل ديموجرافية واجتماعية، مثل السكن (ريف أو حضر)، والمستوى التعليمي للوالدين، والحالة الاقتصادية، مع التركيز على أن هذه الظاهرة تبرز بوضوح أكبر في المجتمع الريفي، يعتمد البحث على بناء نموذج رياضي إحصائي يربط بين ثلاثة متغيرات أساسية: متوسط عدد المواليد في الأسر التي لم تشهد وفيات، واحتمالية وفاة الطفل، واحتمالية اتخاذ قرار بإنجاب طفل بديل (الاحتمال التعويضي)، ويقترح الباحث استخدام "المتغيرات الصورية" لقياس تأثير التعليم ومحل الإقامة على هذه المعلمات، مؤكداً في الختام أن تطبيق هذا النموذج يتطلب توفير بيانات ضخمة من خلال عينات عشوائية واسعة، وهو ما يمكن تحقيقه بدمج هذه الأسئلة ضمن استمارات التعداد السكاني القومي لضمان دقة المؤشرات التخطيطية. This research presents an analytical study of the phenomenon of "compensatory desire," which is the tendency of families to have more children to compensate for the loss of children at a young age. This leads to high fertility rates that hinder development plans in Egypt. The research shows that this response varies from one family to another based on demographic and social factors, such as residence (rural or urban), the parents' educational level, and economic status, with the emphasis that this phenomenon is more pronounced in rural communities. The research relies on building a mathematical statistical model that links three key variables: the average number of births in families that did not experience deaths, the probability of child death, and the probability of deciding to have a replacement child (the compensatory probability). The researcher suggests using "dummy variables" to measure the impact of education and place of residence on these parameters. The research concludes by emphasizing that applying this model requires providing large datasets through extensive random sampling, which can be achieved by integrating these questions into the national population census forms to ensure the accuracy of the planning indicators.